Natural gas as an instrument of Russian state power - Ghaleb, Alexander (Letort paper, 2011)
This monograph is meant to provide an unbiased examination of: the scarcity of natural gas in the contemporary security environment; the salience of natural gas in Russia's national security strategies; and, the natural gas pipeline politics in Eastern and Central Europe. While the tendency of most energy security scholars has been to collectively analyze Europe's dependency on oil and gas, this author analyzes the two energy markets separately, and demonstrates that natural gas is a more potent instrument of coercion in the contemporary security environment than oil was in the traditional security environment. Sufficient evidence is also provided that Russia continues to perceive NATO as a hostile alliance, and that future natural gas disruption by Russia -- which holds a monopoly on the supply of natural gas via pipeline to Eastern and Central Europe -- will prove deadly to the economies of many NATO member states. The salience of natural gas as an instrument of state power is emphasized in Russia's negotiations with Ukraine; this monograph credits the 2006 and 2009 gas wars between the two nations as the main causes for the failure of the Orange Revolution in Ukraine. Ultimately. today, Russia uses the same tools it used in Ukraine -- in the context of natural gas negotiations -- to bribe Western European nations; to divide the NATO Alliance; and to rule over its traditional sphere of influence in Eastern and Central Europe. Finally, the author emphasizes that with the Russian construction of Nord Stream and South Stream natural gas pipelines, and unless alternatives to Russian natural gas are found, it is only a matter of time until Russia will use natural gas as an instrument of coercion against NATO member states